2013
DOI: 10.1185/03007995.2013.858621
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of treatment and monitoring patterns and subsequent outcomes among patients with chronic myeloid leukemia treated with imatinib in a community setting

Abstract: Almost one-third of patients initiating imatinib for CP-CML required dose modification, treatment interruption, or discontinuation. Opportunities for improved monitoring in this setting were identified. Limitations include those inherent to retrospective analyses based on EMR and the uncertain extrapolability of the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…[19][20][21][22] In the present analysis, the effectiveness of first-line TKIs was investigated in community-based oncology practices. Specifically, we evaluated response rates, adherence, and all-cause discontinuation in patients with CML.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] In the present analysis, the effectiveness of first-line TKIs was investigated in community-based oncology practices. Specifically, we evaluated response rates, adherence, and all-cause discontinuation in patients with CML.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31] The availability of multiple TKI treatment choices and the emergence of deep molecular responses as a treatment goal have increased the importance of accurate, precise, and sensitive measurement of BCR-ABL1. Although a number of challenges remain, [13] the widespread adoption of the IS in the United States is an important step toward global standardization of CML data reporting.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a chart review analysis found that patients with frequent molecular monitoring per ELN guidelines during the first year of treatment were less likely to progress or die on study. [28] A separate chart review analysis found that patients who had 1-2 or 3-4 BCR-ABL1 RQ-PCR tests per year experienced a lower risk of progression than patients who had no BCR-ABL1 RQ-PCR tests. [29] Regular molecular monitoring in patients with CML is also associated with improved treatment compliance [30] and economic benefits.…”
Section: Molecular Monitoring In Cml: Importance and Current Recommenmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of frequent monitoring of treatment response in patients with chronic myeloid leukemia (CML) is well established . Timely adjustment of tyrosine kinase inhibitor (TKI) therapy in patients with a failing response is essential to prevent progression from chronic to advanced stage disease as this carries a poor prognosis.…”
Section: Introductionmentioning
confidence: 99%